KECERDASAN BUATAN DALAM PEMBELAJARAN MATEMATIKA: MENINGKATKAN EFEKTIVITAS LAYANAN PENDIDIKAN PUBLIK - Adinda Beauty Afnenda; Rifda Izza; Nanang Hadi Hariyanto; Aulia Rahmatika Nur Azizah; Litsa Nailul Fauziyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students often consider mathematics a difficult subject; however, there is great potential to improve the quality of learning when artificial intelligence (AI) technology is applied in education. The purpose of this study is to examine the ability of AI to improve mathematics learning and consider public education. This study focuses on two main areas: first, how AI can improve students' understanding of mathematical concepts in a more interactive and adaptive way; and second, the extent to which AI contributes to ensuring equitable access and improving educational service standards. Overall, this study finds that artificial intelligence technology has a significant impact in the context of education in helping students understand mathematical concepts and providing learning experiences that are tailored to students' needs. In line with this, AI also helps public education services through inclusive and interactive distance learning services. The two main challenges that need to be addressed are the preparation of digital infrastructure and the preparation of educators. Based on the above reasons, the conclusion that can be drawn is that AI technology has high potential to improve the quality of mathematics learning and public services in the region.